Use of Recycling Building Demolition waste As Coarse Aggregate in Hot Mix Asphalt - Nabil I. Al- Sarrag* Hanaa Khaleel A Suham E. Saleh Al-Maliky (Tikrit Journal of Engineering Sciences, 2014)
At the recent years in Iraq, building demolition increase because of wars and the processes of destruction that lead to increase concrete waste, causing extreme pressure on the available land-filled sites that’s becomes a new challenge to local environment, in addition to south region from country poor from aggregate source.  So this study make as first evaluation to return use concrete aggregate for old and demolition building in concrete asphalt mix, the concrete aggregate obtained from building to live long more than 20 years after crash reinforcement concrete and sieving to get requirement granular particle to make locally asphalt mixture (Type IIIB) depends on modified specification of State Commission of Roads and Bridges (2003) with percent (0,25,50,75,100)% from weight of coarse aggregate.  Asphalt mixtures were tested by Marshall test, Indirect tensile strength test, and the loss of stability test.